AN OVERVIEW OF FLEXIBLE HUMAN RESOURCE MANAGEMENT AND THE ROLE OF INNOVATIVE WORK BEHAVIOR - Dr. N. Roopalatha,; Dr.P. Sridhar, (The journal of contemporary issues in business and government, 2022)
The relationship between flexible HRM, innovative work behaviours, and company innovation is the topic of this research. A theoretical framework was established based on a thorough study of current literature to show the relationship between these factors, namely Flexible HRM, Innovative Work Behaviour, and Company Innovativeness. Flexible HRM (HR practises flexibility, employee skill flexibility, and employee behavioural flexibility) and company innovativeness (Product innovation, Process innovation, and administrative innovation) are all interconnected.